Utilization Of Soymilk As Milk Replacer For Calves - Masum, AKM; Islam, MN; Khan, MAS (Bangladesh Journal of Animal Science, 2012)
An experiment was conducted to study the utilization of soymilk as milk replacer for raising calves. Nine crossbred calves were selected and divided into three groups on the basis of their body weight and genotype. The calves of group A were reared by cow milk, group B reared by strained soymilk and group C reared by unstrained soymilk. It was found that, total body weight gain of group A, B and C were 13.933 ± 1.222, 13.800 ± 0.917 and 13.233 ± 1.537 Kg, respectively. There was no significant difference among the three groups of calves. Non-significant differences were also seen for increment in wither height (5.588 ± 0.508, 5.419 ± 0.529 and 5.080 ± 0.440 cm, respectively), length (6.096 ± 0.440, 5.927 ± 0.388 and 5.503 ± 0.388 cm, respectively) and heart-girth (5.842 ± 0.440, 5.588 ± 0.916 and 5.419 ± 0.388 cm, respectively) of calves. Economic analysis showed that soymilk was cheaper than cow milk (Tk. 8.0 vs Tk. 44.0). It can be concluded that soymilk as milk replacer could be used successfully for raising dairy calves. DOI: http://dx.doi.org/10.3329/bjas.v38i1-2.9918 BJAS 2009; 38(1-2): 102-107